2018
DOI: 10.2337/dc17-1536
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Symptoms in Diabetes: Prevalence, Assessment, Pathogenesis, and Management

Abstract: If you haven't measured something, you really don't know much about it.-Karl Pearson (attributed)Gastrointestinal (GI) symptoms represent an important and often unappreciated cause of morbidity in diabetes, although the significance of this burden across the spectrum of patients and the underlying pathophysiology, including the relationship of symptoms with glycemic control, remain poorly defined. The relevance of GI symptoms and the necessity for their accurate assessment have increased with the greater focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 90 publications
6
107
0
10
Order By: Relevance
“…Diabetic gastroparesis is a condition characterized by upper gastrointestinal (GI) symptoms and delayed gastric emptying (GE) without gastric outlet obstruction . In addition to potentially debilitating symptoms of nausea, vomiting and upper abdominal pain, the condition may have profound implications for the patients’ ability to regulate their blood glucose levels . Delayed GE is associated with both short‐ and long‐term hyperglycemia .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic gastroparesis is a condition characterized by upper gastrointestinal (GI) symptoms and delayed gastric emptying (GE) without gastric outlet obstruction . In addition to potentially debilitating symptoms of nausea, vomiting and upper abdominal pain, the condition may have profound implications for the patients’ ability to regulate their blood glucose levels . Delayed GE is associated with both short‐ and long‐term hyperglycemia .…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition to potentially debilitating symptoms of nausea, vomiting and upper abdominal pain, the condition may have profound implications for the patients' ability to regulate their blood glucose levels. 2,3 Delayed GE is associated with both short-and long-term hyperglycemia. 4 Gastroparesis may also influence the absorption of oral medications, emphasizing the need for reliable, inexpensive, and accessible tests for measuring GE.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed significantly higher scores of gastrointestinal profile (characterized by chest pain, feeling of fullness, nausea, gastroesophageal reflux, pain or discomfort in the abdomen, constipation, diarrhea, bloating or swelling of the abdomen, anal pain) in diabetic patients with anxiety and depression than in controls and other diabetic patients. It is reported that gastrointestinal symptoms occur more frequently in both type 1 and type 2 diabetic patients, who exhibit higher levels of psychosocial problems [36,37]; psychological disorders, including anxiety and depression, are strongly associated with gastrointestinal symptoms [37]. On the other hand, acute changes in blood glucose concentration affect gastrointestinal motor function and increase perceptions of nausea, fullness, and bloating [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that gastrointestinal symptoms occur more frequently in both type 1 and type 2 diabetic patients, who exhibit higher levels of psychosocial problems [36,37]; psychological disorders, including anxiety and depression, are strongly associated with gastrointestinal symptoms [37]. On the other hand, acute changes in blood glucose concentration affect gastrointestinal motor function and increase perceptions of nausea, fullness, and bloating [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…17 Apart from them, diabetes also increases susceptibility to cognitive decline, cancer, infections and gastrointestinal disease. 18,19 Only 5% of people have type 1 diabetes (T1D). 20 Patients who develop T2D are generally sedentary and obese.…”
Section: Introduction 1global Burden Of Metabolic Diseasesmentioning
confidence: 99%